English Language Learning Anxiety at SMP Muhammadiyah Tanjungpinang: A case study: A case study - Eka Mayasari; Joko Iswanto (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This qualitative case study investigated the factors and impacts of English language learning anxiety among students at SMP Muhammadiyah Tanjungpinang. The research focused on students from the 7th, 8th, and 9th grades during the academic year 2024/2025. A total of 32 students across all grade levels were involved in the study. The researchers initially conducted classroom observations to identify students who exhibited signs of anxiety during English lessons. Based on these observations, eleven students were selected as participants for semi-structured interviews and more detailed classroom observations. The research aimed to explore how anxiety manifests in the classroom and how it affects students' language acquisition in a unique socio-educational environment. The data collected through interviews and observations were analyzed qualitatively by interpreting students’ responses and behavioral patterns in class. The findings revealed that three primary types of language anxiety—Communication Apprehension, Test Anxiety, and Fear of Negative Evaluation—were commonly experienced by the students. These forms of anxiety were often interconnected, compounding the emotional barriers students faced in English learning. One of the key contributing factors was the students’ fear of peer ridicule, especially within a tightly bonded student community. Many of the participants were affiliated with orphanages connected to the school, which created a unique emotional and social environment. This setting, while supportive in many ways, also contributed to heightened sensitivity to peer judgment and a strong fear of making mistakes. As a result, the affective filter among these students was notably high, significantly hindering their willingness to participate and ultimately affecting their English language acquisition.